2023
DOI: 10.3389/fpsyg.2022.1052737
|View full text |Cite
|
Sign up to set email alerts
|

Impact of social media-supported flipped classroom on English as a foreign language learners’ writing performance and anxiety

Abstract: As flipped classroom has received much attention from researchers and educators, some scholars have investigated the effectiveness of this teaching mode in various English as a foreign language (EFL) settings; however, such an instruction mode has been under-investigated in the Chinese EFL context. Therefore, the current study examined a flipped course’s impact on Chinese EFL learners’ writing performance and anxiety utilizing a pretest-posttest non-equivalent group quasi-experimental design. First, it selecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 80 publications
1
1
0
Order By: Relevance
“…The contributions of TPD-FLACW empirically verify what is transcribed by the pedagogical theories of socioconstructivism (Vygotsky et al, 1978), constructionism (Gergen, 2007), and connectivism (Siemens & Fonseca, 2007) in the processes of academic writing: planning, textualization, and revision (Cassany & García, 1999;Flower & Hayes, 1981). Furthermore, the findings are consistent with research indicating the significant impact of FL (Daulay et al, 2021;Ebron & Mabuan, 2021;Khojasteh et al, 2021;Mohammad & Khan, 2023;Montaner-Villalba, 2021;Zhao & Yang, 2023) or CW (Baldwin et al, 2019;Ebadi & Rahimi, 2019;Moore & Chaisson, 2022) on the production of academic texts. Studies that attempted to implement collaborative work in a FL model also found consistent results in written expression (Roohani & Rad, 2022;Shafiee Rad et al, 2022).…”
Section: Discussionsupporting
confidence: 75%
“…The contributions of TPD-FLACW empirically verify what is transcribed by the pedagogical theories of socioconstructivism (Vygotsky et al, 1978), constructionism (Gergen, 2007), and connectivism (Siemens & Fonseca, 2007) in the processes of academic writing: planning, textualization, and revision (Cassany & García, 1999;Flower & Hayes, 1981). Furthermore, the findings are consistent with research indicating the significant impact of FL (Daulay et al, 2021;Ebron & Mabuan, 2021;Khojasteh et al, 2021;Mohammad & Khan, 2023;Montaner-Villalba, 2021;Zhao & Yang, 2023) or CW (Baldwin et al, 2019;Ebadi & Rahimi, 2019;Moore & Chaisson, 2022) on the production of academic texts. Studies that attempted to implement collaborative work in a FL model also found consistent results in written expression (Roohani & Rad, 2022;Shafiee Rad et al, 2022).…”
Section: Discussionsupporting
confidence: 75%
“…Our findings suggest that distractions, lack of focus, and limited speaking and interaction opportunities are among the main challenges faced in teaching and learning via social media-based microlearning for English speaking. Future research could focus on addressing these issues by integrating new technologies or teaching paradigms, such as AI-assisted English speaking practice (Zou, Du, et al, 2023), social media-based collaborative learning (Ansari & Khan, 2020), and social media-supported flipped classroom models (Fan, 2022;Zhao & Yang, 2023). Further investigations may help realize the goals of providing engaging content and fostering a supportive community, as outlined by the helpful suggestions identified in this study.…”
Section: Implications and Future Researchmentioning
confidence: 96%
“…FL is a form of blended learning where students engage with online materials before class and then participate in hands-on activities during in-person sessions (Bergmann & Sams, 2012). A fundamental aspect of FL is the transition that occurs when students access instructional videos or online resources remotely, which they study before class to apply during their in-person sessions (Chang, 2023;Zhao & Yang, 2023).…”
Section: Flipped Learningmentioning
confidence: 99%